Approaches to international relations - Chan, Stephen, 1949-; Moore, Cerwyn; Sage eBooks (London : SAGE, 2009)
This four-volume set includes seminal journal articles and book excerpts dealing with various approaches to international relations theory selected and introduced by the editors.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: International relations; Electronic books